Hak Asasi Manusia atas Lingkungan yang Aman bagi Kehidupan dan Kesehatan: Peraturan Hukum, Tantangan Kontemporer dan Perspektif Komparatif - Leheza, Yevhen; Sinkevych , Olena; Kravtsova, Zorina; Kudriavtseva, Olena; Cherniak , Ievgeniia (Universitas Islam Negeri Antasari Banjarmasin, 2023)
Abstract: The purpose of the research is to disclose human rights to an environment safe for life and health. Main content. The article reveals relationship between the concepts of “human rights” and